Answer:
parametric equation: q = (2-t)x + (2+t)y + (3-4t)z
symm equation:
![(x-2)/(-1) = (y-2)/(1) = (z-3)/(-4)](https://img.qammunity.org/2020/formulas/mathematics/college/bsq7dmcfhli87grek477vunp083xdnxdn5.png)
Explanation:
Parametric equation is just like the point slope equation:
y= b + mx
but in this case we have multiple variable so it'll be
q= p₀ + dt
p₀ will be any of your point. d will be the vector containing points shared by both your vector. It can be found by subtracting your two points together.
t is just an arbitrary variable.
Solve for d=p₂ - p₁ , you can also do d=p₁ - p₂
Now plug it into your q= p₀ + dt equation.
You can plug p₂ or p₁ in for p₀. I used p₁.
The result should give you the parametric equation.
Now solve for all of them in term of t. This step is just basic algebra.
since they're all t=..., then you can set them all equal to each other to get the symmetric equation.